Clay soil chronic kidney failure in Vidharbha region of Maharashtra state - Himmatrao Saluba Bawaskar; Pramodini Himmatrao Bawaskar; Parag Himmatrao Bawaskar; Pankaj Himmatrao Bawaskar (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Background: Chronic Kidney Diseases (CKD) is not uncommon in farmers working in a clay soil land in Buldana, amarvati and Akola districts called kharpan patta Maharashtra state India. We surveyed incidence of CKD in 246 villages. Methods and patients: We visited the villages were from CKD farmers are reported to media or news papers or reported in literature . Details were discussed with heads of village. On previous day of visit evening announced by head of villages the information regarding those families with history CKD ,other kidney problems or if any suspicions of CKD or member died of CKD, all the family members are invited for clinical examination, with available reports of CKD patients. Clinically suspected or known CKD patient's blood, urine, drinking water and soil were investigated for content of heavy metals. The pesticide and manure used for farming were also studied.  Results: Total 21,006 villagers from 246 villages were surveyed for CKD of a clay soil region. 372(18/10000), 497(214/1000), 1559(74/1000), 150(7.1/1000) had CKD, renal calculi, impending renal failure and died respectively. Sixty patients were investigated of these forty had raised serum creatinine of 1.7-11mg/dl (mean 4.94). lead, copper, cadmium were present in urine, blood . drinking water and soil. lead and copper content pesticides are routinely sprayed on crops. Cadmium contaminated phosphate manure are sprayed over crops for to increased yield. Cadmium adsorbed over clay soil and released in drinking source of water, lead percolated in soil to drinking water. Interpretation: Clay soil responsible for CKD in farmers. Drinking water sources are contaminated with cadmium and lead responsible for CKD in clay soil region.